EFEKTIFITAS PEMBERIAN TERAPI KOMPLEMENTER JAMU KUNYIT DAN KENCUR PADA IBU NIFAS UNTUK MENINGKATKAN VOLUME ASI DI WILAYAH KERJA PUSKESMAS TAPIN UTARA - Dzul Hidayani, Yunisa; Maolinda, Winda; Mahdiyah, Dede (LPPM Universitas Sari Mulia, 2023)
Background:Breast milk (ASI) is the best method of feeding for infants. The coverage of exclusive breastfeeding at the Tapin Utara Health Center is still below the target, which may be due to insufficient breast milk production. Asitri is a compound known to enhance breast milk production, and it is found in turmeric and kencur (aromatic ginger). Objective:To examine the effect of turmeric and kencur herbal medicine (jamu) on increasing breast milk volume in postpartum mothers in the working area of the Tapin Utara Public Health Center. Method:This was an experimental study using a quasi-experimental design with a one-group pre-test and post-test approach. Postpartum mothers were divided into an intervention and a control group. Sampling was done using purposive sampling. Data were analyzed using a paired t-test. Results:Univariate analysis based on age showed that all 10 respondents (100%) were in the low-risk age category. Regarding the postpartum day, the most common was day three, with 5 respondents (50%) in both groups. Bivariate analysis showed a p-value of 0.000 (<0.05), indicating a significant effect of turmeric and kencur herbal medicine on improving breast milk production in postpartum mothers in the Tapin Utara Health Center working area. Conclusion:There was an increase in breast milk volume of 120 ml after 7 days of administering turmeric and kencur herbal medicine, indicating its effectiveness in increasing breast milk volume in postpartum mothers in the Tapin Utara Health Center area, Tapin Regency. Keywords: Turmeric Herbal Medicine, Kencur (Aromatic Ginger), Complementary Therapy, Postpartum, Breast Milk Volume